Knowledge, attitude, and practices regarding proton pump inhibitors among community pharmacists and pharmacy students - Hamurtekin, E.; Bosnak, A. S.; Azarbad, A.; Moghaddamshahabi, R.; Hamurtekin, Y.; Naser, R. B. (Wolters Kluwer Medknow Publications, 2023)
Background: There are concerns about inappropriate use and insufficient knowledge of proton pump inhibitors (PPIs) use among medical staff. Aims: This study was designed to examine pharmacy students' and community pharmacists' knowledge, attitude, and practices toward PPIs and their relationship with specific sociodemographic characteristics. Subjects and Methods: This descriptive study was conducted on the pharmacy students (first and last year) at Eastern Mediterranean University and community pharmacists in North Cyprus Data were collected by a validated questionnaire, which assessed knowledge, attitude, and practices regarding PPI use. Students were included without sampling in a volunteer-based manner. Registered community pharmacists were selected randomly. Results: First-year pharmacy students (n = 77) showed significantly lower knowledge levels than last-year students (12.00 vs. 13.65; P < 0.001); however, there was no significant difference between last-year students (n = 111) and community pharmacists (n = 59). First-year pharmacy students were significantly less aware of PPIs' dosage and administration than the other two groups. Last-year students and community pharmacists exhibited significantly higher attitude scores regarding PPI use (24.7 and 24.6 vs. 22.7; P < 0.001). Omeprazole was found to be the most preferred PPI among the three studied populations. Community pharmacists used PPIs mainly to treat acid reflux. Gender, nationality, and pharmacy education program type did not influence pharmacy students' knowledge, attitude, or practices. Conclusions: There was not a significant difference regarding knowledge and attitude between the last-year pharmacy students and community pharmacists. The practices of community pharmacists were significantly different from the pharmacy students. It was concluded that certain essential topics regarding PPI use should be emphasized in pharmacy education and during pharmacy practice. Further, it is essentially important for community pharmacists to continue their education through training programs after graduation to enhance their knowledge of PPI use.
Keywords: Attitude; community pharmacist; knowledge; pharmacy student; practices; proton pump inhibitor